Employment and Welfare: A Review of the Literature on Socioeconomic Implications - Desi Yuniarti; Surya Budimansyah; Endar Purnawan (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research explores the relationship between employment and well-being through an in-depth literature review to understand the socioeconomic implications. Wellbeing in the workplace encompasses aspects of mental health, security, and rewards for work, all of which contribute significantly to employee productivity and satisfaction. The findings suggest that promoting well-being in the workplace can increase employees' contribution to the organization, reduce absenteeism and turnover, and support sustainable economic growth. In addition to the impact on individuals and organizations, workplace well-being also has far-reaching effects on society, such as reduced burden on public health systems and improved quality of life in working communities. Therefore, investing in employee well-being programs not only benefits companies but also advances overall socio-economic development. In conclusion, optimizing workplace well-being through inclusive and sustainable policies and practices is a strategic move that promotes social responsibility while creating a competitive advantage.